# Solve the equation. y + 3 = -y + 9

y = 1, y = 3, y = 6, y = 9

**Solution:**

Given y + 3 = -y + 9

In order to find the value of y, we need to isolate the variable 'y'

Let us solve the equation using the transposing method.

Hence, bringing -y from right to left side of equation and shifting 3 to right

We get,

y+y = 9-3

2y = 6

y=3

## Solve the equation. y + 3 = -y + 9

y = 1, y = 3, y = 6, y = 9

**Summary: **

Thus, by solving the equation y + 3 = -y + 9, we get y=3.

Math worksheets and

visual curriculum

visual curriculum